Child care, parental labor supply and tax revenue - Martin Eckhoff Andresen; Tarjei Havnes (Statistics Norway, Research Department, 2018)
We study the impact of child care for toddlers on the labor supply of mothers and fathers in Norway. For identification, we exploit the staggered expansion across municipalities following a large reform from 2002. Our IV-estimates indicate that child care use causes an increase in the labor supply of mothers. Results suggest that cohabiting mothers move towards full time employment, while single mothers move to part time. Meanwhile, we find no impact for fathers or grandparents. We also find an increase in the taxes paid from cohabiting mothers, lending some support to the argument that parts of the cost of child care is offset by increased taxes.
Keywords: H24; H52; J13; J22; 330; Child care; female labor supply; tax revenue; instrumental variables